Mapping students' thinking structure in solving PISA-like problems: Errors and defragmentation - Wahab A, Abdul; Buhaerah, Buhaerah; Ahsan, Muhammad; Busrah, Zulfiqar (Universitas Islam Negeri (UIN) Mataram, 2023)
[English]: Errors in problem-solving indicate that there is a part of the thinking structure that is problematic, either because it is disorganized, disconnected, or experiencing cognitive holes. This research explores students' thinking structure errors in solving PISA problems and proposes defragmentation efforts to address these issues. The study participants consisted of three high school grade X students with varying abilities high, medium, and low selected through purposive sampling. Data collection involves tests and semi-structured interviews, with triangulation used to ensure data validity. The analysis includes presenting test results and interview transcripts, thorough examination of sheets and transcripts, categorization of thinking structure errors, and elaboration of defragmentation efforts based on problem-solving stages. The study findings identify variations in thinking structure errors and defragmentation strategies among participants. This research shows the importance of teaching with a focus on strengthening understanding of prerequisite concepts, improving reading literacy skills, and diversifying defragmentation approaches, especially in applying scaffolding-explaining strategies, to improve the quality of students' mathematical problem-solving. [Bahasa]: Kesalahan dalam pemecahan masalah menunjukkan bahwa ada bagian struktur berpikir yang bermasalah, baik karena tidak teratur, terputus atau mengalami lubang kognitif. Penelitian ini mengeksplorasi kesalahan struktur berpikir siswa dalam menyelesaikan masalah PISA dan mengusulkan upaya defragmentasi untuk mengatasi masalah tersebut. Partisipan penelitian terdiri dari tiga siswa kelas X SMA dengan kemampuan berbeda-beda, yaitu tinggi, sedang, dan rendah, yang dipilih melalui purposive sampling. Pengumpulan data dilakukan dengan tes dan wawancara semi terstruktur, dengan triangulasi digunakan untuk menjamin keabsahan data. Analisisnya meliputi penyajian hasil tes dan transkrip wawancara, pemeriksaan lembar dan transkrip secara menyeluruh, kategorisasi kesalahan struktur berpikir, dan penjabaran upaya defragmentasi berdasarkan tahapan pemecahan masalah. Temuan penelitian mengidentifikasi variasi kesalahan struktur berpikir dan strategi defragmentasi di antara para peserta. Penelitian ini menunjukkan pentingnya pengajaran dengan fokus pada penguatan pemahaman konsep prasyarat, peningkatan keterampilan literasi membaca, dan diversifikasi pendekatan defragmentasi, khususnya dalam penerapan strategi scaffolding-explaning, untuk meningkatkan kualitas pemecahan masalah matematika siswa.